Mapping the Location of Disaster Posts as a Flood Disaster Mitigation Effort in Comal District: Pemetaan Lokasi Posko Bencana sebagai Upaya Mitigasi Bencana Banjir di Kecamatan Comal - Shobiroh, Anti Amania (Prosiding University Research Colloquium, 2023)
This research aims to analyze mitigation efforts in handling flood disasters in Comal District for disaster preparedness. The method used to determine the location of disaster posts uses Buffer Proximity Analysis with ArcGIS 10.8 software. The research results were then analyzed using qualitative descriptive methods. The data used in this research is secondary data. Secondary data was obtained through documents held by agencies related to the flood disaster. Efforts that need to be made when floods occur every year, disaster mitigation is necessary so that survivors know evacuation locations if a disaster occurs. From these results it is known that the number of accessible disaster posts obtained was 19 locations consisting of places of worship and educational facilities that were not affected by areas prone to flooding.